Memorandum of Understanding between the International Livestock Research Institute (ILRI) and Mettu University - International Livestock Research Institute; Mettu University (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Memorandum of understanding (MoU) between the International Livestock Research Institute (ILRI) and Mettu University. On March 11, 2022, MoU was signed by Jimmy Smith, Director-General of ILRI, and Endegena Abebe, President of Mettu University.